1987
DOI: 10.1002/ijc.2910390610
|View full text |Cite
|
Sign up to set email alerts
|

Hot beverages and oesophageal cancer in southern brazil: A case‐control study

Abstract: There is a cluster of high-incidence areas of oesophageal cancer in south-eastern South America, including Southern Brazil, Uruguay and parts of Argentina. The present case-control study investigated the hypothesis that this may be due to the drinking of maté, a traditional beverage drunk at a very high temperature, and also studied the role of other known risk factors such as alcohol and tobacco. Cases (171) and age- and sex-matched controls (342) were recruited from hospitals in the State of Rio Grande do Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
14

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 12 publications
4
66
0
14
Order By: Relevance
“…Previous studies on foods and risk of squamous cell oesophageal cancer (Victora et al, 1987;Brown et al, 1998;Bosetti et al, 2000;Castellsagué et al, 2000) displayed stronger effects of fruits compared with vegetables. It is possible that cooked vegetables are not associated with squamous cell of the oesophagus due to temperature of the water.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies on foods and risk of squamous cell oesophageal cancer (Victora et al, 1987;Brown et al, 1998;Bosetti et al, 2000;Castellsagué et al, 2000) displayed stronger effects of fruits compared with vegetables. It is possible that cooked vegetables are not associated with squamous cell of the oesophagus due to temperature of the water.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies on oesophageal cancer reported a final model including nondietary and dietary factors (Victora et al, 1987;Castelletto et al, 1994;Launoy et al, 1998;Cheng et al, 2000;Sharp et al, 2001). In our final model, which excluded nondietary factors, citrus fruits were the more significant and stronger term (P-value for trend o0.001), followed by stewed meat (P-value ¼ 0.007) and Foods and squamous cell oesophageal cancer E De Stefani et al fresh vegetables (P-value ¼ 0.009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A evidente relação dose-resposta para os diferentes níveis de exposição ao fumo e à bebida fortalece a hipótese de que esses fatores têm importante papel na etiologia dessa doença. Achados semelhantes foram encontrados por outros pesquisadores 1,16,23,24,27,32,34 . Tuyns 30 (1990) destaca que o álcool é um dos poucos exemplos de substâncias químicas que parecem estar claramente envolvidas em certos tipos de câncer em humanos, especialmente os de boca, laringe, hipofaringe e esôfago, sem ter sido possível demonstrar esse fato em estudos experimentais.…”
Section: Comentáriosunclassified
“…O papel de diferentes fatores tem sido estudado: a influência de fatores genéticos, condições anormais do esôfago, hábitos tais como beber, fumar e mascar, consumo de alimentos em temperaturas extremas, dietas, condição socioeconômica e fatores ocupacionais, além do efeito de radiações ionizantes, da composição do solo, do clima e da vegetação. As evidências apontam para uma doença que é característica de locais com precárias condições socioeconômicas e dieta deficiente e que tanto o álcool como o fumo têm papel importante no aparecimento do tumor em várias partes do mundo 5,12,15,21,25,29,32,33 .…”
unclassified